Family members' perceptions of older person discharge from emergency departments. (4th February 2021) - Fry, Margaret; Elliott, Rosalind; Curtis, Kate; Mei, Joy; Fitzpatrick, Lesley; Groth, Rachel; Murphy, Sandra; Jones, Keryn; Hofman, Catherine
Abstract: Background: People aged over 64 years account for approximately 20% of adult emergency presentations, with up to 60% of people discharged home from emergency departments (EDs). Many older people discharged home are supported by family. Objectives: The objective of this study was to explore the family members' perspectives of older people's discharge from ED to inform new alternative or innovative models of care. Methods: The design was a descriptive exploratory study. A convenience sample of family members was recruited from three EDs across Sydney, New South Wales. Telephone interviews were conducted over a six‐month period and data were analysed using statistics or thematic analysis. Results: Interviews were conducted with 133 family members of whom the majority were female ( n = 80, 60%) with a median age of 70 years (IQR 91–35). Over 87% of family members were satisfied with ED care and discharge processes that were provided to the older person. The majority ( n = 129, 97%) of family members reported that they understood the treatment and perceived that the older person's condition was well managed ( n = 119, 86%). The majority ( n = 114, 86%) of family members reported being informed of the medical diagnosis and were confident (87%, n = 115) to continue care of the older person at home. Three themes emerged from qualitative data: (a) a sense of time—moving through ED; (b) giving voice to the impact of clinician communication; and (c) the delivery of comfort and basic care. Discussion: Family members reported that they were engaged in and satisfied with the older person's ED treatment and discharge. However, family members suggested that there was opportunity to improve communication consistency for ED discharge and managing the wait. Conclusion: Clinicians need to engage with family members to optimise quality and safety. Clinicians need to understand that family members considered comfort and fundamentals of care to be an important dimension of the older person's ED management plan.